EFEKTIVITAS PEMBELAJARAN IPA MENGGUNAKAN MEDIA POWTOON DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR - Hamidaturrohmah Hamidaturrohmah (Tunas Nusantara, 2019)
Learning media is one important component that can help teachers in the learning process and can attract the attention of students to learn. This study aims to examine the effectiveness of the use of powtoon audiovisual media to improve student learning outcomes in science subjects at SD N 2 Ngabul Annual Jepara. The method used in this study is quasi-experimental (quasi experiment research). This quasi-experimental study is conducted by giving treatment to a class, hereinafter referred to as the experimental class, which will be compared with the control class. The research subjects were grade IV SDN 2 Ngabul. The average pretest learning outcomes of the experimental group students was 58.89 and the control group was 56, 94 while the average posttest learning outcomes of the experimental group was 76.94 and the control group was 71.11. Based on the independent sample t test with a significance level α = 5%, the value obtained is 0.040> 0.05 with the value of t count> t table is 2.128> 2.101 then Ho is rejected and Ha is accepted, meaning that there is a significant difference between the experimental group learning outcomes and group. This shows that the use of powtoon audiovisual media is effective in improving student learning outcomes in the content of science lessons in elementary school.